KINERJA KEUANGAN PEMERINTAH KABUPATEN MANOKWARI DITINJAU DARI DERAJAT OTONOMI FISKAL DAN INDEKS KEMAMPUAN RUTIN - Johanes Paulus Koromath (Fakultas Bisnis UKDW, 2016)
This study aims to analyze the financial capability of Manokwari regency government seen from theratio of the degree of fiscal autonomy and capability index ratio routine. The data used are secondarydata include the data of the Regional Income (Pendapatan Daerah), the realization of Local OwnRevenue (Pendapatan Asli Daerah), and Routine Expenditures (Belanja Rutin) in 2010 through 2014.Data analysis using financial ratio analysis. The results of this study showed that the degree of fiscalautonomy Manokwari district is at the low category. It is seen that in the mean is 3.00% or at veryless or categories range 0.00% to 10.00%.Furthermore Routine capability index is in the lowcategory. It is seen that in the mean is 16.5% or are at very less or categories range 0.00% to 20.00%.Keywords: regional income, local own revenue, routine expenditures